Job satisfaction and employee engagement: A study of Sudanese workers in Saudi Arabia - Ahmed, Noha Khalifa Seddig; Arabi, Nahla G A (International Journal of Management and Sustainability, 2025)
This study explores the relationship between job satisfaction and employee engagement among Sudanese employees working in the Kingdom of Saudi Arabia. It examines how intrinsic and extrinsic job satisfaction contribute to engagement, emphasizing cultural and social factors influencing expatriate workers. Using a quantitative cross-sectional approach, the research investigates how intrinsic and extrinsic job satisfaction influence engagement. Data were collected from 146 respondents through a structured questionnaire, and multiple regression analysis was conducted to assess the predictive role of intrinsic and extrinsic job satisfaction on employee engagement. The results show that 51.1% of the variance in employee engagement (R² = 0.511) is explained by intrinsic and extrinsic job satisfaction. Intrinsic job satisfaction appeared as a stronger predictor (Beta = 0.523, p < 0.001) compared to extrinsic job satisfaction (Beta = 0.276, p < 0.001). The findings indicate that employees who derive personal meaning from their work are more likely to be engaged, emphasizing the importance of intrinsic factors such as recognition and personal growth in fostering employee engagement. While extrinsic factors such as salary and job security also contribute, their impact is relatively weaker. Cultural factors, including job security concerns and workplace respect, further shape engagement levels. Improving job satisfaction through competitive compensation, professional growth opportunities, and a supportive work environment can significantly enhance engagement. Understanding expatriates’ unique motivators is vital for reducing turnover and improving performance. Organizations should adopt culturally sensitive strategies that address the specific needs of Sudanese expatriates, focusing on fair treatment, job security, and career development to maximize engagement. Future research should explore moderating factors such as leadership style and organizational culture.